Nature and mechanism of the in vivo oligomerization of nucleoid protein H-NS - Stella, Stefano (Nature Publishing Group, 2005)
Two types of two-hybrid systems demonstrate that the transcriptional repressor, nucleoid-associated protein H-NS (histone-like, nucleoid structuring protein) forms dimers and tetramers in vivo, the latter being the active form of the protein. The H-NS ‘protein oligomerization' domain (N-domain) is unable to oligomerize in the absence of the intradomain linker while the ‘DNA-binding' C-domain clearly displays a protein–protein interaction capacity, which contributes to H-NS tetramerization and which is lost following Pro115 mutation. Linker deletion or substitution with KorB linker abolishes H-NS oligomerization. A model describing H-NS dimerization and tetramerization based on all available data and suggesting the existence in the tetramer of a bundle of four α-helices, each contributed by an H-NS monomer, is presented.